Free vibration and buckling characteristics of laminated composite and sandwich plates implementing a secant function based shear deformation theory. (February 2015) - Grover, Neeraj; Singh, Bhrigu N; Maiti, Dipak K
A generalized finite element modeling of recently developed secant function based shear deformation theory is formulated and implemented for free vibration and buckling characteristics of laminated-composite and sandwich plates. The shear deformation is expressed in terms of a secant function of thickness coordinate. The theory inherently satisfies the zero transverse shear conditions on top and bottom surfaces of the plate. An eight-noded C 0 continuous element is chosen by an adequate choice of nodal field variables. The governing equations are obtained for the free vibration and buckling responses of laminated-composite and sandwich plates. Intensive numerical experiments are conducted to investigate the influence of span-thickness ratio, boundary conditions, etc. on the free vibration and buckling behavior. The comparison of present results with the published results indicates the performance and range of applicability of the present theory in the framework of finite element analysis.